2006
DOI: 10.1007/s00425-006-0445-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lead-regulated genes by suppression subtractive hybridization in the heavy metal accumulator Sesbania drummondii

Abstract: Heavy metal contamination of soils is of widespread occurrence as a result of human, agricultural and industrial activities. Among heavy metals, lead is a potential pollutant that readily accumulates in soils and sediments. Although lead is not an essential element for plants, it gets easily absorbed and accumulated in Sesbania drummondii, which exhibits a significant level of tolerance to lead. The response of a metal tolerant plant to heavy metal stress involves a number of biochemical and physiological path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 45 publications
0
23
0
Order By: Relevance
“…By comparing the abundance of a housekeeping gene b-tubulin before and after subtraction, we found the subtraction efficiency of the libraries was high. SSH based on suppression PCR is a good method to find genes differentially expressed in two groups and was used to find genes related to heavy metal tolerance and accumulation in plants in some studies (Srivastava et al 2007;Lewandowska et al 2007;Huang et al 2009a, b).…”
Section: Discussionmentioning
confidence: 99%
“…By comparing the abundance of a housekeeping gene b-tubulin before and after subtraction, we found the subtraction efficiency of the libraries was high. SSH based on suppression PCR is a good method to find genes differentially expressed in two groups and was used to find genes related to heavy metal tolerance and accumulation in plants in some studies (Srivastava et al 2007;Lewandowska et al 2007;Huang et al 2009a, b).…”
Section: Discussionmentioning
confidence: 99%
“…GSH is the direct precursor of phytochelatins (PCs) in a reaction catalyzed by phytochelatin synthase (PCS). It is known that the metal stress alleviates the depletion of GSH [60], and enhance PCs synthesis, resulting in an increased metal tolerance of plants [71]- [73]. Nouairi et al [71], reported that the level of PC-SH in tolerant plants was significantly increased under Cd stress in Brassica juncea.…”
Section: Discussionmentioning
confidence: 99%
“…The cDNAs generated from plants at low P level served as "testers", while cDNAs generated from plants at high P level were used as "drivers". cDNA digestion, adaptor ligation, hybridization, and PCR ampliWcation were done according to the protocol described earlier (Srivastava et al 2007). Subtracted PCR ampliWed cDNAs were cloned into pCRscript vector using TOPO TA Cloning kit (Invitrogen, USA).…”
Section: Construction Of the Suppression Subtractive Hybridization (Smentioning
confidence: 99%
“…In this technique diVerentially expressed genes can be normalized and enriched over 1000-fold in a single round of hybridization (Diatchenko et al 1996). SSH has successfully been used on various plant species to isolate genes involved in responses to biotic and abiotic stresses (Zhang et al 2005;Srivastava et al 2007;Venkatachalam et al 2007). In the present investigation, an attempt was made to isolate P starvation-regulated genes from a P-eYcient common bean genotype (G19833) using SSH analysis.…”
mentioning
confidence: 99%